Behaviour of thermostone blocks with and without cement mortar plastering exposed to high temperatures - Abdulhussein Faisal K. (Institut za istrazivanja i projektovanja u privredi, 2021)
Autoclaved aerated concrete (called Thermostone in Iraq) is one of the popular building materials that are used in various purposes in construction industries. It is factory-made material that can be moulded into blocks which can be used in framework buildings. However, these buildings are under the risk of fire since it has different cusses such as arson and electrical short circuit. It is important to find ways to improve counter such phenomenon. Therefore the objective of this paper is investigating the fire resistance performance of Thermostone with and without plastering. Five different samples were used for the test, four of them were covered with different types of plastering. Three tests were employed for this study: Compressive, absorption, and density test. For all tests, the samples were exposed to elevated temperatures from 250°C to 900°C. It was shown that the compressive strength are reduced when exposed to high temperature by up to 75%, however the air-cooled samples are less affected by approximately 15%. Furthermore, plastered samples has lower absorption rate than non-plastered ones. Finally, density decrease with heat by up 10% approximately.